Monitoring Roof Displacements with GPS in a Long Period Structure - Sayim, Irfan; Akbas, Bulent; Doran, Bilge (TURKISH CHAMBER CIVIL ENGINEERS, 2012)
Monitoring Roof Displacements with GPS in a Long Period Structure Relative displacements play an important role in assessing drift and damage distribution in structures. GPS technology has gained great attention in the last decade for static and dynamic structural monitoring of displacements in long-period structures as an alternative. In this study, roof displacements of a long-period structure with a total of 31-story located at Maslak, Istanbul were monitored under deforming effects such as wind using real-time kinematic (RTK) differential GPS (DGPS) technology. The DGPS system was first tested on a prototype, and then assembled on the building. The structural model of the building was also constructed and periods were estimated and the compared with GPS related estimation results due to the modal analysis of building.
Keywords: DGPS; structural monitoring; relative displacements; roof displacement; high-rise buildings; Engineering